ARTIFICIAL INTELLIGENCE AS A METHODOLOGICAL INNOVATION IN THE TRAINING OF FUTURE DESIGNERS: MIDJOURNEY TOOLS - Ivan M. Tsidylo; Chele Esteve Sendra (Інформаційні технології і засоби навчання)
Applications of artificial intelligence are used in almost all spheres of human activity. Their use in the educational process at all levels of education is no exception. The article discusses the possibility of using a new generation of artificial intelligence Midjourney tools in the process of training future designers. A review of 2022 releases for creating complex, abstract or photorealistic images Stable Diffusion, DALL-E 2 and Midjourney. The analysis showed that Midjourney is most suitable for using artificial intelligence tools as a methodological innovation in training. The presence of an extended instruction on the formation of a prompt for the generation of an image stimulates non-standard new ways of thinking and allows you to expand the imagination of future design specialists. Midjourney developers recommend structuring the prompt by Subject, Medium, Environment, Lighting, Color, Mood, Composition. You can also use images from the Internet or add your own images. Any subscriber gets access to the gallery of Midjourney members. A survey of art students was conducted regarding the formation of a description of the proposed images. The result of image generation according to the students’ description using the Midjourney tool is given. The analysis of the answers confirms our assumptions about the need to form fundamental knowledge of the principle of operation of the image generation application; insufficient knowledge in visual arts as such; low ability to integrate knowledge of, one might say, opposite fields - art and exact sciences (mathematics, artificial intelligence, etc.); the lack of skills in formulating a description of images through the expression of the main categories of visual art through the linguistic means of language, whether in English or in the mother tongue. Such a situation prompts the selection of methods and means for developing the ability to carry out a qualitative verbal description of images and the surrounding reality in order to popularize the possibility of using artificial intelligence technologies in the process of training future designers.